2020
DOI: 10.3390/toxics8040115
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disruption: Structural Interactions of Androgen Receptor against Di(2-ethylhexyl) Phthalate and Its Metabolites

Abstract: Diethylhexyl phthalate (DEHP) is a commonly used plasticizer in the manufacture of polyvinyl chloride plastics for household and commercial use. DEHP is a ubiquitous ecocontaminant and causes developmental and reproductive problems in children and adults. After exposure, DEHP is metabolized by endogenous hydrolysis and oxidation into the primary metabolite, mono-(2-ethylhexyl) phthalate (MEHP), and the secondary metabolites, mono-(2-ethyl-5-hydroxhexyl)phthalate (5-OH-MEHP), mono-(2-ethyl-5-oxohexyl) phthalate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Also, DMEHE was identified in ethyl acetate leaf extract of Amaranthus viridis (58.52%) which exhibited an antifungal activity (Akbar et al, 2020), and a strong larvicidal activity against Spodoptera exigua (Lepidoptera) (Rachokarn et al, 2008). Pure DMEHE caused human endocrine disruption (Beg & Sheikh, 2020), cytotoxic (Krishnan et al, 2014), antibacterial (Verma et al, 2014), and antifungal (Akpuaka et al, 2012) activities. Also, DMEHE as the main di(2‐ethylhexyl) phthalate metabolite, is a known reproductive toxicant (Kalo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Also, DMEHE was identified in ethyl acetate leaf extract of Amaranthus viridis (58.52%) which exhibited an antifungal activity (Akbar et al, 2020), and a strong larvicidal activity against Spodoptera exigua (Lepidoptera) (Rachokarn et al, 2008). Pure DMEHE caused human endocrine disruption (Beg & Sheikh, 2020), cytotoxic (Krishnan et al, 2014), antibacterial (Verma et al, 2014), and antifungal (Akpuaka et al, 2012) activities. Also, DMEHE as the main di(2‐ethylhexyl) phthalate metabolite, is a known reproductive toxicant (Kalo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…BPA and DEHP are classified as EDs that mimic, block or interfere with the endocrine system, inducing a diverse array of health issues. BPA is a weak estrogen-like compound able to link to estrogen receptor alpha [ 40 ], whereas DEHP can disrupt androgen receptor signaling [ 41 ]. Results obtained with the computational tools contributed to put into evidence that the interactions between compounds are mainly of antagonism type, and it may be in part explained with the different mechanisms at receptor level.…”
Section: Discussionmentioning
confidence: 99%
“…The data have shown that DEHP and its metabolites interacted with the ligand-binding pocket of AR, forming amino-acid residue interactions, hydrogen bonding, and pi-pi interactions. This binding energy of DEHP with AR has been shown to be similar to that of native ligand T, and the amino-acid residue interactions of DEHP metabolites had 91-100% similarity compared to that of T [136]. Therefore, considering the structural binding data, the potential role of DEHP metabolites to disrupt AR signaling has been suggested, which may lead to androgen-related reproductive dysfunction.…”
Section: Pesticides/biocides and Plasticizersmentioning
confidence: 91%
“…An interesting recent in silico docking study has characterized the bond of DEHP and its metabolites with AR to predict the potential endocrine-disrupting effects of these metabolites in AR signaling [136]. The data have shown that DEHP and its metabolites interacted with the ligand-binding pocket of AR, forming amino-acid residue interactions, hydrogen bonding, and pi-pi interactions.…”
Section: Pesticides/biocides and Plasticizersmentioning
confidence: 99%